The development and evaluation of a social bookmarking service prototype for the University of the Philippines Diliman School of Library and Information Studies - Azul, Jason James R.; Cabbab, Johann Frederick A. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2011)
Web 2.0 is a web computing concept that emphasizes the use of the World Wide Web as a platform for giving users full control of content creation and manipulation. Libraries have been using Web 2.0 to reach out to clients, to promote the library and to collect and organize online resources. The UP Diliman Library System uses Web 2.0 technology in the form of blogs, social networking sites and instant messengers for reaching out to clients, for giving online reference services, and for promoting the library and its collection. Under the UP Diliman Library System, The UP School of Library and Information Studies Library use Web 2.0 technology in the form of a social networking site account. This was primarily used as a promotional aid and a place for making inquiries about the library.
A web 2.0 technology called social bookmarking have been utilized by some libraries to build a repository of online resources by letting users submit web links that are relevant to the library's collection. The researcher developed a prototype social bookmarking service website for UPSLIS and was evaluated by BLIS students to know the potential users' reception of the service. The evaluation showed an above average reception for all the categories out of a maximum score of 5 which include website first impressions (3.70), navigation (3.68) and value proposition (3.83). Positive usage behavior was also observed from the evaluation data.
It is recommended to improve the prototype and re-evaluate it using a more significant sample size that includes the faculty, MLIS students and library staff. "
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman). School of Library and InformationStudies -- Students; Bookmarks